Stent grafts for treatment of cannulation zone stenosis and arteriovenous graft venous anastomosis. Issue 1 (March 2017) - Shemesh, David; Goldin, Ilya; Olsha, Oded
Stent grafts (SGs) are widely used for treatment of failing vascular accesses, fistulas and grafts. The mechanical barrier of the covered stent prevents in-stent stenosis and can be used to effectively correct ruptured vein and aneurysms. Treatment of cannulation zone stenosis with SG can be justified when its use is obligatory, in order to prevent total access loss. Although there are worrying complications attendant on SG insertion and cannulation, including jeopardizing future access creation, most studies report no complications of SG in cannulation zone stenosis. SGs for treatment of arteriovenous graft venous anastomosis stenosis is controversial. Two large randomized trials conclusively demonstrate improved primary patency with SGs at the venous anastomosis of arteriovenous graft at up to two years when compared with percutaneous transluminal angioplasty, sustained for up to 2 years and reducing the number of interventions per patient year. However, the ultimate goal of SG treatment of venous anastomosis stenosis is preventing thrombosis and increasing graft longevity, which was unfortunately not fully achieved.